Transumbilical laparoscopy for pneumoperitoneum establishment: a comprehensive multicentre evaluation affirming safety, feasibility, and a range of clinical benefits - Rizzuto, Antonia; Bozzarello, Cristina; Andreuccetti, Jacopo; Amaddeo, Angela; Iannello, Antonio Maria; Sagnelli, Carlo; Cirocchi, Roberto; Cuccurullo, Diego; Pignata, Giusto; Corcione, Francesco (Frontiers in Surgery, 2024)
**Abstract:** This retrospective multicentre study evaluates the safety, feasibility, and clinical benefits of transumbilical laparoscopy (TUL) for establishing pneumoperitoneum in laparoscopic cholecystectomy for gallbladder diseases. A cohort of 2543 patients underwent TUL between 2011 and 2021 across multiple medical institutions in Italy. Data collection encompassed demographic, clinical, intraoperative, and postoperative parameters. Preoperative and postoperative management adhered to standardized protocols. The TUL technique involved precise anatomical incision and trocar placement. Results demonstrated favorable outcomes, including a low conversion rate to open surgery (0.55%), minimal intraoperative complications (0.16%), and short hospital stays (average 2.4 days). Incidence of incisional hernias was notably low (0.4%). Comparison with existing literature highlighted consistent findings and unique insights. Despite limitations, including the lack of a control group and retrospective nature, the study provides valuable depth to the literature, informing surgical decision-making and advancing patient care in laparoscopic cholecystectomy for gallbladder diseases.